Memaksimalkan Dampak Media Sosial dalam Pemasaran Digital: Strategi Instagram yang Efektif untuk Merek - Rahman, Fadali; Tzauri, Achmad; Khoiruddin; Pradana, Ferry (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Instagram has emerged as a crucial tool for social media marketing, as it enables businesses to connect with their target audience in the contemporary digital landscape. This study examines the most effective strategies businesses have employed to enhance audience engagement and growth on Instagram. A qualitative technique was employed to assess the strategies implemented by 22 leading digital marketing companies in the Madura market, drawing on insights from specialists inside these agencies. The data indicate that the majority of marketing experts consider Instagram to be the essential medium for communication and marketing tactics. This underscores Instagram's efficacy in social media marketing efforts and its pivotal role in corporate marketing strategies. Nonetheless, despite the favorable rating, several experts expressed their dissatisfaction with certain characteristics, including navigation, limited visibility, high costs relative to outcomes, ad fatigue, and a narrow emphasis on the business-to-business sector. Conversely, Instagram is esteemed for its ability to engage stakeholders and achieve operational objectives. This overview underscores the importance of a planned and comprehensive approach on Instagram, focusing on innovation, audience engagement, and the quality of shared content.